2011
DOI: 10.5625/lar.2011.27.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic and Non-traumatic Osteonecrosis in the Femoral Head of a Rabbit Model

Abstract: Osteonecrosis of the femoral head is an idiopathic, debilitating and progressive disease. A number of traumatic or non-traumatic animal models have been reported for research on osteonecrosis. This study was performed to compare the efficacy of femoral head osteonecrosis in rabbits by traumatic and non-traumatic methods. Twenty-seven New Zealand White rabbits were divided into three experimental groups, nine heads each. Two groups were surgically induced into osteonecrosis; a steel cerclage wire was ligated ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Furthermore, in the femoral head ultrastructure necrosis, osteoblast-like cell death and lysis were also identified (14). This indicated that femoral head necrosis is closely associated with the change in the number of bone cells.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, in the femoral head ultrastructure necrosis, osteoblast-like cell death and lysis were also identified (14). This indicated that femoral head necrosis is closely associated with the change in the number of bone cells.…”
Section: Discussionmentioning
confidence: 83%
“…Another method to disturb vascularization of the femoral head has also been suggested by Hwang et al (2). In that study, after the proximal femur was exposed to create traumatic ANFH, a tight cerclage wire was wrapped around the femur necks of one group of rabbits, while a cerclage wire was wrapped around the femur necks of another group and electric current was given to this wire by monopolar cautery.…”
Section: Discussionmentioning
confidence: 99%
“…Femoral head osteonecrosis is a common disease, affecting the relatively young population (2). Although its pathomechanism has not been definitively elucidated, it is assumed that there is an ischemic factor and blood loss problem in both traumatic and non-traumatic femoral head osteonecrosis (2). Pathologies caused by different etiologies are similar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations